Respon Al-Quran dalam Menyikapi Berita Hoax - Chalimatus Sa'diyah (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2020)
This article aims to analyze the Qur'an's response in responding to hoax news. hoax information dissemination on social media is a phenomenon that threatens ukhuwah Islamiyah in the nation and state. The existence of hoax content in the universe of social media has a significant negative impact that has succeeded in making the community divided, such as making proactive content, propaganda, turning facts around. The author uses the maudhu'i method as the blade of his analysis. The results of this study conclude that God condemns the perpetrators of hoaxes spreaders. The Koran also recommends always telling the truth. He is the act of those who obey God. By maintaining the correct words, the spread of hoaxes will be increasingly minimal. Furthermore, besides saying the truth, the Koran and the hadith also instructed Muslims to always do tabayyun or clarification of the arrival of the news. Even this clarification is also very directed at religious leaders to always oversee the arrival of the news and clarified the truth.